Estudo para dois violinos de Samuel Cavalcanti: investigação de estratégias violinísticas e estudo analítico voltado ao ato interpretativo - Freire, Flávia de Castro Machado (2022)
The present research consists of an investigation of the conventions concerning the role of the musician, guided by the reflection on the interpretive act. Therefore, the detailing of some concepts and terms, within the making of music, is a fundamental part of its methodological path. In this discussion, subtleties that transcend instrumental performance were sought, such as understanding the composer's intentions, the freedom given to the interpreter, the idea of fidelity to the work, the importance of the cultural context in which the composer and the work are inserted. The subject of this research is the Study for Two Violins, by the brazilian composer Samuel Cavalcanti, who was born in the state of Paraíba, northeast of Brazil. In order to research and verify the concepts related to the present discussion, we revisited two video performances recorded previously. The main theoretical support related to the interpreter's role before a musical work are texts by Stravinsky (1996) and Schoenberg (2001), while Harnoncourt (1998) will be related to the cultural context of music in society. The research was also conducted by observing and writing down details of technical and relational processes employed during the interpretive construction of the performances. Therefore, the act of interpreting after the perspective of the musician himself was highlighted. In this sense, the autoethnographic account of the experiences of this researcher, who is also a violinist and interpreter of these two performances, constitutes the main source of this research. The case in analysis passes through the actual subjects of the action, through the investigation of the practices related to the performances of the piece, as well as the universe among interpreters, composer, score and the musical understanding of the work. This research stands by its potential in sharing the results with those who may include this work in their repertoires or take advantage of the methodology used for the elaboration of other interpretations, especially in the contemporary musical context. Finally, we highlight the dedication and incessant search of the musicians – who take advantage of artistic freedom without opposing submission to the work conceived by the composer – which is considered as indispensable and important characteristics of the interpretive act.